Risk Management Impact on the Legal Challenges of Fast-Track Projects in Dubai - ZAKI, MOHD (2018)
This thesis is about the impact of the risk management on the legal challenges of the fast-track construction projects. The focus of the study is to identify the risk factors from different stake holders (client, consultant, contractor and sub-contractor) involves in the execution of the projects and could impact on the legal challenges of the fast track project in Dubai and to develop the operative risk management framework to resolve the risk factors and their impact on the factors of legal challenges. To achieve the goal mixed method of analysis used. Data collected via literature review of books, articles specifically related to fast track projects, legal challenges involves in the fast track project and risk management methods implementation in Dubai construction industries and further questionaries’ developed based on the literature review. And questionnaire distributed among the professionals working in the fast-track project as client, consultant and contractors (sub-contractor) and their response analysed using the techniques of statistics. The results demonstrated the significant risks are related either clients or contractor. Finding shows project management team has the knowledge about the risk management but poor implementation of the same. The study shows that poor implementation of the risk management in the fast-track could leads to divesting legal challenges which may affect the project execution. The aim is to establish and prove that effective risk management can reduce the number of legal challenges for successful construction project in the Dubai.